Irradiation effects on Gd3Al2Ga3O12 scintillators prospective for application in harsh irradiation environments. (November 2019) - Auffray, E.; Dosovitskiy, G.; Fedorov, A.; Guz, I.; Korjik, M.; Kratochwill, N.; Lucchini, M.; Nargelas, S.; Kozlov, D.; Mechinsky, V.; Orsich, P.; Sidletskiy, O.; et al.
Abstract: We provide evidences that multicomponent garnet-type Ce-doped crystal GAGG (Gd3 Al2 Ga3 O12 ) is a promising scintillator to be applied in harsh irradiation environments, particularly, in high-energy physics experiments and reactor research facilities, where long-term operation is mandatory. Applicability of this scintillator for the upgrade of the detectors at future accelerators with high luminosity like High luminosity LHC is considered and GAGG:Ce with different codopings is compared with Ce-doped oxyorthosilicate crystals, which are currently also strong candidates for such applications. It is shown that the irradiation with 24 GeV protons at a fluence of 5x10 14 p/cm 2 has no significant effect on optical absorption in the spectral range of the scintillator emission. The contribution of radioisotopes formed in the material by irradiation with protons to the noise pedestal and the noise energy equivalent due to harmful radio-luminescence excited by the radionuclides remains negligible at short gates in collider experiments. Moreover, we show that the irradiation-generated color centers absorb outside the spectral range of Ce luminescence. These centers do not significantly affect the dynamics of nonequilibrium carriers, which is responsible for the timing properties of the scintillator. The density of free carriers decays with a characteristic time of 2 ps, while the decay constant for trapped carriers is ∼50 ns both before and after irradiation. Highlights: Luminescence intensity due to hadron-induced isotopes is similar in GAGG and LSO. Proton fluence of up to 5x1014 p/cm2 does not affect timing properties of GAGG:Ce. GAGG is prospective for radiation detectors in harsh radiation environments.